KEBIJAKAN PEMBIAYAAN KREDIT PERUMAHAN RAKYAT (KPR) SEJAHTERA SUSUN SEBAGAI SOLUSI KEBUTUHAN PERUMAHAN MASYARAKAT BERPENGHASILAN RENDAH (MBR) PADA BANK TABUNGAN NEGARA (BTN) CABANG SOLO BERDASARKAN PERATURAN MENTERI NOMOR 3 TAHUN 2014 TENTANG FASILITAS LIKUIDITAS PEMBIAYAAN PERUMAHAN DALAM RANGKA PENGADAAN PERUMAHAN MELALUI KREDIT/PEMBIAYAAN PEMILIKAN RUMAH SEJAHTERA (FLPP) - Nandanita Satriavie, Bagas Akhmad Adi Nugroho (GEMA, 2015)
Either national or international instruments mandate countries to fulfil housing rights for their citizen. One of things done by Indonesian government is through publishing Peraturan Menteri Nomor 3 Tahun 2014 tentang Fasilitas Likuiditas Pembiayaan Perumahan Dalam Rangka Pengadaan Perumahan Melalui Kredit/Pembiayaan Pemilikan Rumah Sejahtera (FLPP). Based on that regulation, for low income societies are given housing facility either KPR Sejahtera Tapak or KPR Sejahtera Susun. However, the program encouraged right now is KPR Sejahtera Susun, remembering in 2015 KPR Sejahtera Tapak will be deleted. This program is implemented by some banks given trust by government which one of the executing banks is BTN. This research takes place in BTN Solo Branch to analize how much the public interest to take advantage of this program. The result showed just a few low income societies in Solo use this program because of many practical threats. Yet, the threats is found the solutions so in the next, program KPR Sejahtera Susun can be taken advantaged by Masyarakat Berpenghasilan Rendah (MBR) optimally.